Rio de Janeiro 2016: Visual and Audiovisual Narratives of the City from both Hegemonic media and Citizen Media - Espinosa, Julian (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
Throw the analyses of how Rio de Janeiro city has been represented by audiovisual formats during Olympic games in 2016, studying products and process of participatory video made by local children and young people, and analyzing the ways how the city is represented in an audiovisual way by commercial spots of International Olympic Committee (IOC), the author identifies mediations (Martin-Barbero) between ways how the city is narrated by both hegemonic media and citizen media way. Article identifies as well visual narratives strategics that offers a complex panorama about politics relationships and ways to face the visual experience of the city. Research opperates using Misè en Scene as analytic operator of televisual style analysis of the selected videos (from both hegemonic and citizen media), combining this methodology with a etnographical process of observation of the process of audiovisual creation in citizen media.